Cultural Sensitivity and Legal Approaches to Forced Marriage: A Comparative Study of Legal Systems in the Subcontinent (Journal of Asian Development Studies, 2023)
Forced marriage, a violation of human rights, remains a pressing concern within the subcontinent, notably in India, Pakistan, and Bangladesh. This abstract concisely overviews the extensive literature review on "Cultural Sensitivity and Legal Approaches to Forced Marriage: A Comparative Study of Legal Systems in the Subcontinent." The research presents key findings from the existing literature, underscoring the pivotal role of cultural sensitivity in addressing forced marriages. Balancing cultural traditions with the protection of human rights emerges as a central challenge, and the effectiveness of legal measures varies across these nations. The review demonstrates that forced marriage is unequivocally recognized as a human rights violation, leading to severe psychological and physical consequences for its victims. Importantly, it suggests the potential for cultural awareness programs, implemented with sensitivity, to reduce forced marriages. This synthesis provides a foundation for further research, emphasizing the need for comprehensive, comparative studies to navigate the complexities of forced marriage and safeguard the rights of women and girls in the subcontinent.